2006
DOI: 10.1086/504516
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Spectroscopy of Carbon Stars in the Small Magellanic Cloud

Abstract: We have observed a sample of 36 objects in the Small Magellanic Cloud (SMC) with the Infrared Spectrometer on the Spitzer Space Telescope. Nineteen of these sources are carbon stars. An examination of the near-and mid-infrared photometry shows that the carbon-rich and oxygen-rich dust sources follow two easily separated sequences. A comparison of the spectra of the 19 carbon stars in the SMC to spectra from the Infrared Space Observatory (ISO) of carbon stars in the Galaxy reveals significant differences. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
158
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(184 citation statements)
references
References 53 publications
23
158
3
Order By: Relevance
“…The theoretical work of Mattsson et al (2008) and Wachter et al (2008) showed that the mass-loss rates of carbon stars may not be sensitive to metallicity. Numerous recent studies using Spitzer spectra of AGB stars in low-metallicity Local Group galaxies (e.g., Sloan et al 2006;Zijlstra et al 2006;Lagadec et al 2007;Matsuura et al 2007;Sloan et al 2008) seem to support this claim. Similar results were obtained by Groenewegen et al (2007), who found in their modeling of the IRS spectra of 60 carbon stars in the Magellanic Clouds that the trend of mass-loss rates with period of luminosity was comparable to that of Galactic sources.…”
Section: Introductionmentioning
confidence: 89%
“…The theoretical work of Mattsson et al (2008) and Wachter et al (2008) showed that the mass-loss rates of carbon stars may not be sensitive to metallicity. Numerous recent studies using Spitzer spectra of AGB stars in low-metallicity Local Group galaxies (e.g., Sloan et al 2006;Zijlstra et al 2006;Lagadec et al 2007;Matsuura et al 2007;Sloan et al 2008) seem to support this claim. Similar results were obtained by Groenewegen et al (2007), who found in their modeling of the IRS spectra of 60 carbon stars in the Magellanic Clouds that the trend of mass-loss rates with period of luminosity was comparable to that of Galactic sources.…”
Section: Introductionmentioning
confidence: 89%
“…This is very different for AGB stars (see the spectrum of an AGB star SMP SMC 18 in Fig. 10, bottom), which show featureless continuum-dominated spectra (Yang et al 2004;Sloan et al 2006). Post-AGB stars (also called photo-planetary nebulae, proto-PNe) show some nebular emission lines and/or PAH features (see the spectrum of post-AGB star IRAS 01005+7910 in Fig.…”
Section: Host Galaxy Contributionmentioning
confidence: 96%
“…Fortunately, other programs produced a surplus of carbon stars, which has resulted in a series of papers on carbon stars in the SMC (Sloan et al 2006b;Lagadec et al 2007) and the LMC Leisenring et al 2008). Three of the peak-up failures resulted in serendipitous observations.…”
Section: Sample Selectionmentioning
confidence: 99%
“…We used CASPIR ( McGregor et al 1994) on the 2.3 m telescope at SSO to obtain images at J (effective wavelength 1.24 m), H (1.68 m), K (2.22 m), and narrowband L (3.59 m). Sloan et al (2006b) describe the calibration methods. Table 3 presents the photometry.…”
Section: Near-infrared Photometrymentioning
confidence: 99%
See 1 more Smart Citation